Impact of frequency of denture cleaning on microbial and clinical parameters – a bench to chairside approach. Issue 1 (1st January 2019) - Ramage, Gordon; O'Donnell, Lindsay; Sherry, Leighann; Culshaw, Shauna; Bagg, Jeremy; Czesnikiewicz-Guzik, Marta; Brown, Clare; McKenzie, Debbie; Cross, Laura; MacInnes, Andrew; Bradshaw, David; Varghese, Roshan; et al.
ABSTRACT: Objective : Robust scientific and clinical evidence of how to appropriately manage denture plaque is lacking. This two-part study (i) developed an in vitro model of denture plaque removal, and (ii) assessed effectiveness of these approaches in a randomised clinical trial. Method : (i) a complex denture plaque model was developed using the dominant microbial genera from a recent microbiome analyses. Biofilms formed on polymethylmethacrylate were brushed daily with a wet toothbrush, then either treated daily for 5 days or only on Days 1 and 5 with Polident® denture cleanser tablets (3 min soaking). Quantitative and qualitative microbiological assessments were performed. (ii), an examiner-blind, randomised, crossover study of complete maxillary denture wearers was performed (n = 19). Either once-daily for 7 days or on Day 7 only, participants soaked dentures for 15 min using Corega® denture cleansing tables, then brushed. Denture plaque microbiological assessment used sterilized filter paper discs. Results : The in vitro model showed daily cleaning with denture cleanser plus brushing significantly reduced microbial numbers compared to intermittent denture cleaning with daily brushing (p < 0.001). The clinical component of the study showed a statistically significant reduction in denture plaque microbial numbers in favour of daily versus weekly treatment (aerobic bacteria p = 0.0144). Both in vitro and in vivo studies showed that denture plaque biofilm composition were affected by different treatment arms. Conclusions : This study demonstrated that daily denture cleansing regimens are superior to intermittent denture cleansing, and that cleansing regimens can induce denture plaque compositional changes. Trial registration: ClinicalTrials.gov identifier: NCT02780661.